2021
DOI: 10.5468/ogs.21176
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor laterality in advanced ovarian cancer

Abstract: This study aimed to investigate the effect of incorporating tumor laterality into the International Federation of Gynecology and Obstetrics (FIGO) staging system for advanced ovarian cancer. MethodsThe clinical data of 131 patients with advanced ovarian cancer treated between 2008 and 2018 were retrospectively reviewed. To investigate the prognostic significance of tumor laterality, we divided the patients into unilateral and bilateral groups. The prognostic significance of tumor laterality (bilateral vs. unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
2
2
0
1
Order By: Relevance
“…This finding matched the study by Momenimovahed et al, (2019) and Badmann et al, (2020), with 70% of cases typed as serous neoplasm (Momenimovahed et al, 2019;Badmann et al, 2020). On the other hand, Yamada et al, (2021) study demonstrated less incidence of serous neoplasm was 52% of total cases and 40% of unilateral ovarian cancer. Sixty-five percent of cases in our study were presented at FIGO stage III.…”
Section: Discussionsupporting
confidence: 88%
“…This finding matched the study by Momenimovahed et al, (2019) and Badmann et al, (2020), with 70% of cases typed as serous neoplasm (Momenimovahed et al, 2019;Badmann et al, 2020). On the other hand, Yamada et al, (2021) study demonstrated less incidence of serous neoplasm was 52% of total cases and 40% of unilateral ovarian cancer. Sixty-five percent of cases in our study were presented at FIGO stage III.…”
Section: Discussionsupporting
confidence: 88%
“…Asymmetries in morphology and function in the left and right adrenals may lead to a higher incidence of unilateral adrenal adenomas on the left side compared to the right. In cancers of other paired organs, including the breast, kidney, and ovary, similar lateralizing asymmetries were also observed, leading scientists to consider laterality as an independent prognostic factor in these cancers [36][37][38].…”
Section: Discussionmentioning
confidence: 85%
“…Sel, et.al obtained the same results in samples of unilateral epithelial ovarian cancer, generally found to be more on the left side (61.5%), no research explains the cause [19]. Univariate and multivariate analysis studies by Yamada et.al on ovarian cancer in general with 131 samples consisting of 58 bilateral samples and 73 unilateral samples (54.8% right samples and 45.2% left samples) did not show any significant differences in overall survival (OS, P=0.218) and progression-free survival (PFS, P=0.604) in right vs left unilateral, but there was a difference in unilateral vs bilateral where OS and PS in unilateral were longer [21]. However, in a study with a larger sample by Zhang et.al on 1483 samples of unilateral MOC, there was no significant difference in incidence between the right (50.8%) and left (49.2%) sites [22].…”
Section: Discussionmentioning
confidence: 85%